2020
DOI: 10.1177/1060826520918323
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Facets of Narcissism, Symptoms of Eating Disorders, and Symptoms of Muscle Dysmorphia

Abstract: Previous research exploring the relationship between muscle dysmorphia, drive for muscularity, and disordered eating behaviors in relation to personality characteristics, particularly narcissism, has yielded interesting, though often conflictual, results. This study explores these relationships through assessing muscle dysmorphia, drive for muscularity, and disordered eating in relation to grandiose and hypersensitive narcissism. Participants included 173 male college students who were recruited via department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…So far, only a few studies have investigated the association of muscularity-oriented body image concerns and narcissism. One study found a more pronounced drive for muscularity in men with higher levels of grandiose narcissism (Littrell et al, 2020), whereas another did not find such a correlation (Davis et al, 2005). For women, grandiose narcissism was also significantly related to drive for muscularity, whereas vulnerable narcissism, on the other hand, was not (Gordon & Dombeck, 2010).…”
Section: The Relations Between Narcissism and Body Image Concernsmentioning
confidence: 99%
“…So far, only a few studies have investigated the association of muscularity-oriented body image concerns and narcissism. One study found a more pronounced drive for muscularity in men with higher levels of grandiose narcissism (Littrell et al, 2020), whereas another did not find such a correlation (Davis et al, 2005). For women, grandiose narcissism was also significantly related to drive for muscularity, whereas vulnerable narcissism, on the other hand, was not (Gordon & Dombeck, 2010).…”
Section: The Relations Between Narcissism and Body Image Concernsmentioning
confidence: 99%
“…Individuals with high levels of narcissism can invest in physical appearance and physical exercise in an attempt to strengthen or enhance their sense of self-worth (Gordon and Dombeck, 2010;Miller and Mesagno, 2014). In this direction, some evidence suggests a possible relationship between narcissism and drive for muscularity (Littrell et al, 2020); however, the literature on the relationship between narcissism and muscle dysmorphic symptoms is scarce and inconclusive (Kuennen and Waldron, 2007;Littrell et al, 2020), and calls for further investigation. On the contrary, if standards are not or only partially met, shame prevails and persists, with serious consequences on of non-training men.…”
Section: Participantsmentioning
confidence: 99%
“…Some authors suggest considering two subtypes of narcissism: grandiose and vulnerable. Grandiose narcissism, a core feature of narcissistic personality disorders (American Psychiatric Association, 2013), is characterised by a profound need for admiration, grandiose thought and behaviours, lack of empathy, an apparent security in social relations, and an intolerance of criticism and a tendency to devalue others (Littrell et al, 2020;Pincus and Lukowitsky, 2010). Vulnerable narcissism, on the other hand, is characterised by a poor self-image, anxiety in social relationships, hypersensitivity to the judgment and opinions of others.…”
Section: Tab 8 Statistics Of Main Effects Of Group and Bdi-ii Scorementioning
confidence: 99%
See 1 more Smart Citation
“…So far, only a few studies have investigated the association of muscularity-oriented body image concerns and narcissism. One study found a more pronounced drive for muscularity in men with higher levels of grandiose narcissism [ 67 ], whereas another did not find such a correlation [ 55 ]. For women, grandiose narcissism was also significantly related to drive for muscularity, whereas vulnerable narcissism, on the other hand, was not [ 5 ].…”
Section: Introductionmentioning
confidence: 99%